1996
DOI: 10.1113/jphysiol.1996.sp021633
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the response of the isolated sino‐atrial node of the rabbit to vagal stimulation.

Abstract: 1. The effects of brief postganglionic vagal nerve stimulation on electrical activity in different regions of the rabbit sino-atrial node and surrounding atrial muscle were recorded. 2. At the centre of the node (the leading pacemaker site), the brief stimulation resulted in a large hyperpolarization followed by a depolarization and a shortening of the action potential. All effects were short lasting (time to 90% recovery of membrane potential, 0 8 s). 3. At other sites within the node and in the surrounding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 29 publications
5
28
0
Order By: Relevance
“…9 Western blotting showed a single band at 160 kDa in atrial tissue samples from both control and CHF rats (Fig 5C). This corresponds to the nNOS band in rat cerebellar tissues.…”
Section: Expression Of Neuronal Nitric Oxide Synthasementioning
confidence: 99%
See 3 more Smart Citations
“…9 Western blotting showed a single band at 160 kDa in atrial tissue samples from both control and CHF rats (Fig 5C). This corresponds to the nNOS band in rat cerebellar tissues.…”
Section: Expression Of Neuronal Nitric Oxide Synthasementioning
confidence: 99%
“…In our previous studies on rabbit SA node tissue preparations we have shown that the intervening acceleration is abolished or minimized in the presence of blockers of If, and the secondary slowing is reduced by cutting the atrial muscle away from the SA node. 9,18 The elimination of the intervening acceleration in the CHF rats could be reconciled by an attenuation of the NO-cGMP system, as NO can directly stimulate the spontaneous beating of SA node pacemaker cells though an activation of If. 19 The elimination of the secondary slowing in the CHF rats might be the result of diminished function of vagal nerves in the atrial muscle surrounding the SA node.…”
Section: Possible Mechanism Of Vagal Nerve Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proteins responsible for the tetramers, Kir3.1 (KCNJ3) and Kir3.4 (KCNJ5), were indeed identified by immunofluorescence in rat SA node . Apart from the direct and short lasting hyperpolarizing effect of I K,ACh on the SA node, the increase in I K,ACh in surrounding atrial muscle leads to a longer lasting effect on the SA node by electrotonic interaction (Kodama et al, 1996).…”
Section: Ach-activated Kmentioning
confidence: 99%